2015
DOI: 10.1007/s12134-015-0452-y
|View full text |Cite
|
Sign up to set email alerts
|

Getting Ahead: Educational and Occupational Trajectories of the ‘New’ Second-Generation in Switzerland

Abstract: This paper examines the educational and occupational trajectories among second-generation immigrants of Turkish and Western-Balkan origin in Switzerland. Using a representative sample of 1107 respondents in two Swiss urban areas, the findings reveal that descendants of immigrants have reduced chances to follow a constant successful path from education to occupation, which is mainly determined by parental socioeconomic status. However, young adults of Turkish and Western Balkan origin are significantly more oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
1
16
0
6
Order By: Relevance
“…Three out of ten lower secondary school students are of foreign nationality in Switzerland, and immigrants from the Western Balkans (the successor states of Yugoslavia) and Turkey constitute two of the largest immigrant populations from non-EU countries (Schnell and Fibbi 2016). Both groups include a large proportion of youth.…”
Section: Introductionmentioning
confidence: 99%
“…Three out of ten lower secondary school students are of foreign nationality in Switzerland, and immigrants from the Western Balkans (the successor states of Yugoslavia) and Turkey constitute two of the largest immigrant populations from non-EU countries (Schnell and Fibbi 2016). Both groups include a large proportion of youth.…”
Section: Introductionmentioning
confidence: 99%
“…Keskiner (2015) displayed that parents deployed varying strategies to influence their children's education across distinct education systems; in countries like the Netherlands where their impact is restricted by the system, they could exert less influence on their children's tracking choices. In Switzerland, Schnell and Fibbi (2016) found that young adults of Turkish and Western Balkan origin were more likely than their peers of native origin to be upwardly mobile in the education system (as opposed to starting high) and that parental monitoring and family cohesion played a significant role in regard to upward mobility.…”
Section: Youth Transitions Of Descendants Of Turkish Immigrantsmentioning
confidence: 99%
“…Swiss scholars have repeatedly critiqued these schools for their stigmatising tendencies, and particularly for directing working class and migrant youth into lower qualified educational and vocational tracks (e.g. Del Percio and Duchêne 2014; Schnell and Fibbi 2016). Secondly, within the bridging schools the refugee youth were taught in separate classes.…”
Section: Integration Workmentioning
confidence: 99%